Factors influencing innovative behavior of employees in SMEs in electrical and electronic sector in Malaysia - Yusof, Rosmelisa (2016)
The organisations of Small and Medium Enterprises (SMEs) need to be prepared for the external challenges which are mostly beyond the control of SMEs. One of the challenges faced by the SMEs is related to employee’s low productivity. Hence, SMEs could improve its internal strength in terms of improving the employees work processes. This however, is only effective if the employees are innovatively improving their work. Therefore, this study aims to look at the role of the employee’s intention to engage in innovative behaviour and examined it by using the Theory of Planned Behaviour (TPB) as a theoretical basis. The research employed determinants of attitude, subjective norm and perceived behavioural control to understand employee’s intention to engage in innovative behaviour. Subsequently, this study attempts to assess the influence of factors such as self-enhancement, openness to change, organizational support, leader expectation, self-efficacy and thriving towards the three determinants of TPB (attitude, subjective norm and perceived behavioural control). This study also investigated the relationship between intention and innovative behaviour. Besides, the organizational fairness was added as a moderator to better reflect the impact of intention on innovative behaviour. Lastly, this study also examined the positive outcomes of innovative behaviour (job satisfaction and job performance). The research employed quantitative method to examine the relationship among the variables. The questionnaires were sent to the 382 professional workers of Electrical and Electronic (E & E) SMEs in Malaysia using convenient sampling. A total of 201 completed questionnaires were obtained. The hypothesis in this research was tested using PLS-SEM. The results revealed that three antecedents of attitude, subjective norm and perceived behavioural control affected the employee’s intention and innovative behaviour. Significant results were also found for openness to change, organizational support, leader expectation, self-efficacy and thriving. Unfortunately, the results of self-enhancement and moderator effects were insignificant. Finally, this study managed to show a positive relationship between innovative behaviour and the outcomes variables (job satisfaction and job performance). This thesis contributes to the theoretical and practical aspects of innovative behaviour in the context of E & E SMEs. In general, the study extends the application of TPB in the context of innovative behaviour and provided empirical support that intention leads to innovative behaviour. Thus, innovative behaviour helped the employees to enhance their skills and capabilities, and contribute to better job performance. In short, it is important to ensure the SMEs employees engaged in innovative behaviour, in order to help the organization to increase its productivity and competitiveness.